EDUKASI ANTI-BULLYING UNTUK MEMBANGUN BUDAYA POSITIF DI KALANGAN SISWA SEKOLAH DASAR - Tiara Putri Aziza; Nurfadillah Apriliah; Nurul Istiqamah Ishaq; Muhammad Hakil; Faisal Rifki; Muslim; Muhammad Nawir (STKIP Subang, 2026)
This community service research focuses on the urgency of providing anti-bullying education as a strategic effort to build a positive culture among elementary school students. The phenomenon of bullying, both in verbal, physical, and psychological forms, shows a worrying trend in the school environment and has a serious impact on victims (decreased self-confidence or trauma) and potentially forms a negative culture. The main objective of this activity is to increase students' awareness of the forms and impacts of bullying, instill values of empathy, tolerance, and social responsibility, and create a safe and inclusive learning environment. The activity was carried out at UPT SPF Bawakaraeng 1, targeting 4th and 5th-grade students, using interactive counseling methods (presentations) and mentoring through simulations and educational games. The results show a positive impact, namely an increase in students' understanding of bullying behavior and their ability to identify and apply ways to deal with it, supported by students' active involvement in participatory activities. Evaluation through interactive quizzes indicates that this education is effective not only in increasing knowledge but also in shaping students' positive attitudes towards social interactions. This planned and sustainable anti-bullying education is expected to be the foundation for building a healthy, harmonious school culture that is free from bullying practices. Keywords: education, anti-bullying, positive culture, elementary school